Treatment with Depot Leuprolide Acetate in Girls with Idiopathic Precocious Puberty: What Parameter should be Used in Deciding on the Initial Dose? - Doğuş Vurallı; Ayfer Alikaşifoğlu; İrem İyigün; Dicle Canoruç; Alev Ozon; Nazlı Gönç; Nurgün Kandemir (Galenos Yayincilik, 2020)
Objective:Doses of gonadotropin releasing hormone (GnRH) analogues used to treat idiopathic central precocious puberty (iCPP) vary among clinicians. Study aims were to evaluate the efficacy of a monthly 3.75 mg dose of leuprolide acetate (LA) to suppress the hypothalamo-pituitary-gonadal (HPG) axis in girls with iCPP and to determine factors that may have an impact on the supressing dose.Methods:Study subjects were 220 girls receiving LA for iCPP. LA was started at a dose of 3.75 mg/28 days. Suppression was assessed using the GnRH test at the third month. To assess clinical suppression signs and symptoms of puberty were also evaluated. The dose of LA was increased to 7.5 mg/28 days in those who had a peak luteinising hormone (LH) ≥2 IU/L and in whom adequate clinical suppression of puberty was absent. Receiver operating characteristic curves were used to determine thresholds for clinical and hormonal factors affecting the suppressing dose of LA. Logistic regression analyses were used to investigate thresholds which might differentiate between those requiring high dose for suppression and those in whom lower dose LA was adequate.Results:Peak stimulated LH <2 IU/L was achieved in 88.6% with a dose of LA of 3.75 mg (0.11±0.03 mg/kg). Significant variables for differentiating the two doses were body weight (Wt) of 36.2 kg and/or body mass index (BMI)-standard deviation scores (SDS) of 1.64 (p<0.001). Multiple logistic regressions showed that Wt and BMI-SDS values above thresholds indicated requirement of LA at a dose of 7.5 mg/28 days (p<0.001).Conclusion:Monthly injections of 3.75 mg LA is an effective treatment in the majority of girls with iCPP. However, a higher initial dose may be preferred in patients with a Wt ≥36 kg or BMI-SDS ≥1.6 for effective suppression of the HPG axis.